Ekran kriminal'nykh soobshchenii . Ekran kriminal'nykh soobshchenii . Screen of Criminal Reports . Экран криминальных сообщений - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Police Day and recollections of the Moscow revolt on October 3-4, 1993; absence of the law in the fight against organized crime. День милиции и воспоминания о мятеже в Москве 3-4 октября 1993 года; отсутствие закона по борьбе с организованной преступностью.